Research on the Profit Model Transformation of Chinese Commercial Banks under the Background of Interest Rate Liberalization - LU, Xiaonan (2016)
Currently, Chinese interest rate marketization reform in the money market, interbank lending market and the credit market had completed, interest rate liberalization has entered a critical stage. Commercial banks are still depend on the deposits and loans business income as their main source of revenue. Thus, the traditional profit model that depend on interest spreads income will be hit significantly with the gradually deepened.interest rate liberalization reform. This paper attempts to provide suggestions for banks on profit model transformation under the background of interest rate liberalization through the analysis of current banks’ profit model.